Controlling H3+ Formation From Ethane Using Shaped Ultrafast Laser Pulses - Townsend, Tiana; Schwartz, Charles J.; Jochim, Bethany; P., Kanaka Raju; Severt, T.; Iwamoto, Naoki; Napierala, J. L.; Feizollah, Peyman; Tegegn, S. N.; Solomon, A.; Zhao, S.; Carnes, K. D.; et al. (Frontiers in Physics, 2021)
An adaptive learning algorithm coupled with 3D momentum-based feedback is used to identify intense laser pulse shapes that control H_3^+ formation from ethane. Specifically, we controlled the ratio of D_2H^+ to D_3^+ produced from the D_3C-CH_3 isotopologue of ethane, which selects between trihydrogen cations formed from atoms on one or both sides of ethane. We are able to modify the D_2H^+:D_3^+ ratio by a factor of up to three. In addition, two-dimensional scans of linear chirp and third-order dispersion are conducted for a few fourth-order dispersion values while the D_2H^+ and D_3^+ production rates are monitored. The optimized pulse is observed to influence the yield, kinetic energy release, and angular distribution of the D_2H^+ ions while the D_3^+ ion dynamics remain relatively stable. We subsequently conducted COLTRIMS experiments on C_2D_6 to complement the velocity map imaging data obtained during the control experiments and measured the branching ratio of two-body double ionization. Two-body D_3^+ + C_2D_3^+ is the dominant final channel containing D_3^+ ions, although the three-body D + D_3^+ + C_2D_2^+ final state is also observed.